1989
DOI: 10.2466/pms.1989.68.3c.1131
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Goodenough-Harris Draw-a-Person Test and a Body-Image Test in Costa Rican Children

Abstract: Although researchers have used drawings of the human figure to evaluate body-image in adults and children, test measures of the concepts involved have not been precisely constructed, so the purpose of this study was to estimate the body-image concept relations measured on the Goodenough-Harris Draw-a-Person Test and on the Prueba para Diagnóstico de Imagen Corporal--Universidad Nacional for 90 kindergarten, first and second graders. Factor analyses (sex by grade, 2 x 3; and sex by age, 2 x 7) showed that sex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The Goodenough-Harris system presented the most consistent results, in psychometric terms, with internal consistency ranging from 0.63 to 0.82 and correlations with cognitive measures varying from 0.49 to 0.59 (Carreras et al, 2013;Woodburn & Boschini, 1989). On the other hand, a study by Ritter, Duffey, and Fischman (1974) identified that HFD was not reliable in estimating the intelligence of children in early grades, such as kindergarten.…”
mentioning
confidence: 95%
“…The Goodenough-Harris system presented the most consistent results, in psychometric terms, with internal consistency ranging from 0.63 to 0.82 and correlations with cognitive measures varying from 0.49 to 0.59 (Carreras et al, 2013;Woodburn & Boschini, 1989). On the other hand, a study by Ritter, Duffey, and Fischman (1974) identified that HFD was not reliable in estimating the intelligence of children in early grades, such as kindergarten.…”
mentioning
confidence: 95%